PENERAPAN KESELAMATAN DAN KESEHATAN KERJA PADA PEKERJA BAGIAN PRODUKSI DI INDUSTRI PENCACAH PLASTIK DENGAN MENGGUNAKAN FAULT TREE ANALYSIS - Reiny Myrtanti; Ida Bagus Suardika (JURNAL REKAYASA SISTEM INDUSTRI, 2022)
CV Rabbani is a small industry that is engaged in the processing (chopping) of plastic, with the final product produced in the form of plastic ore. Currently CV Rabbani does not yet have a unit that manages the occupational safety and health (K3) management system and its workers have not been involved in the effort to implement K3, because this business is still a small business and has few human resources (no more than 10 people), and there is still no awareness in implementing K3 in their work environment. Therefore, it is necessary to evaluate and analyze, especially those related to occupational health and safety. The purpose of this study was to determine the process of managing K3 management, the dangers of work accidents and the factors causing work accidents that occurred at CV Rabbani. The method used in this research is Fault Tree Analysis (FTA), which is a method that is easy to apply and is used to identify potential hazards, evaluate the factors causing work accidents in every company activity to reduce the risk of work accidents, and analyze the process of managing the Health and Safety Management System Work by involving workers in the company and it is hoped that zero accidents can be achieved.